2014
DOI: 10.1089/end.2014.0236
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Cystogram Findings Predict Incontinence Following Robot-Assisted Radical Prostatectomy

Abstract: Postprostatectomy bladder neck location defined by the BNPS ratio on cystogram correlates with continence rates and may predict patients at risk for prolonged incontinence. Efforts designed to preserve support of the bladder neck and sphincteric complex in relation to the pubic symphysis may improve both early and late continence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…Several physicians have reported the significant correlation between the postoperative cystogram findings and urinary continence after radical prostatectomy . Olgin et al reported an association between the post‐prostatectomy bladder neck location, defined by the bladder neck to the pubic symphysis (BNPS) ratio, and urinary continence at both 3 and 12 months. They concluded that the bladder neck location and urinary continence after RALP were significantly correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several physicians have reported the significant correlation between the postoperative cystogram findings and urinary continence after radical prostatectomy . Olgin et al reported an association between the post‐prostatectomy bladder neck location, defined by the bladder neck to the pubic symphysis (BNPS) ratio, and urinary continence at both 3 and 12 months. They concluded that the bladder neck location and urinary continence after RALP were significantly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the bladder neck location and urinary continence after RALP were significantly correlated. Ha et al also reported the correlation between the bladder neck location and urinary continence using the BNPS ratio defined by Olgin . They concluded that the BNPS ratio was shown to be an independent predictive factor for urinary continence at 3 months after radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The BNPS ratio in the cystogram has been used to define the bladder neck location and to predict postoperative continence. Olgin et al, first descript the measured method with BNPS in prediction of postoperative continence in patient received radical prostatectomy and reported the continence rate of the lowes BNPS (mean 0.16), intermediate BNPS (mean 0.41) and high BNPS (mean 0.70) group were 80.3%, 72.7% and 59.7%, respectively (8). Our results also confirm the predictive value of the cystogram in the unimultivariate analysis model and this may be used as a tool to predict functional outcome or evaluated anatomic condition of pelvic floor.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of the bladder neck to pubic symphysis (BNPS) ratio in predicting postoperative continence after radical prostatectomy was described and the lower BNPS ratio was associated with a better early continence outcome (8).…”
mentioning
confidence: 99%
“…To identify predictive factors for urinary continence, it was divided into two categories: early continence ( < 3 months) and late continence ( > 12 months) [26].…”
Section: Discussionmentioning
confidence: 99%